The appearing demos Hong Kong during and after the Umbrella Movement - Pang, Laikwan (University of Michigan Press, 2020)
"Studying Hong Kong's Umbrella Movement, which might be the largest Occupy movements in recent years, this books urges us to re-commit in democracy at a time when democracy is failing on many fronts in different parts of the world. The 79-day long Hong Kong Umbrella Movement occupied major streets of the busiest parts of the city, creating tremendous inconvenience to this city famous for capitalist order and efficiency. It is also a peaceful collective effort of appearance, and it is as much as a political event as a cultural event. The urge for expressing an independent cultural identity underlined both the Occupy and the remarkably rich cultural expressions generated. Understanding the specificity of Hong Kong's situations, the book also comments on some global predicaments we are facing in the midst of neoliberalism and populism. It directs our attentions from state-based sovereignty to city-based democracy, and emphasizes the importance of participation and cohabitation. The book also examines how the ideas of Hannah Arendt are useful to those happenings much beyond the political circumstances which gave rise of her theorization. The book will pay particular attentions to the the actual intersubjective experiences during the protest. They are local, fragile, and sometimes inarticulable, therefore resisting rationality and debates, but they define the fullness of any individual, and they also make politics possible. Following the call of David Harvey, we will examine how the right to the city is a viable political project"